Trust region methods for solving multiobjective optimisation - Qu, Shaojian; Goh, Mark; Liang, Bing (Optimization methods & software, 2013)
This paper first proposes a trust region algorithm to obtain a stationary point of unconstrained multiobjective optimisation problem. Under suitable assumptions, the global convergence of the new algorithm is established. We then extend the trust region method to solve the non-smooth multiobjective optimisation problem.